Pengaruh Literasi Keuangan dan Fitur Teknologi Finansial terhadap Keputusan Penggunaan Bank Digital Seabank - Annisa Puspadewi; Chairunisa Nur Fadila; Meautia Hanifah; Nur Hasanah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this study is to examine how students in the 2022–2024 cohorts of the Faculty of Economics and Business (FEB) at Universitas Negeri Jakarta (UNJ) use financial technology features and financial literacy when deciding whether to use digital banking services. Eighty active SeaBank users participated in this study, which uses a quantitative methodology. Multiple regression techniques were used to evaluate the data. With a coefficient value of 0.872, the results show that financial literacy significantly influences usage decisions, while SeaBank's financial technology elements significantly influence usage decisions as well (coefficient value of 0.346). These results show that increasing financial literacy among students and making the most of financial technology features can boost young users' acceptance of digital banking services. The goal of this study is to support the present era's digital financial transformation by providing useful insights for creating marketing strategies and financial education in digital banking.